HUBUNGAN PENGETAHUAN DAN SIKAP PETUGAS KESEHATAN TERHADAP KEPATUHAN MELAKUKAN HAND HYGIENE DI RSUD RAJA AHMAD TABIB TANJUNGPINANG - Apriani, Fitri; Yunita, Prasida (Zona Kebidanan: Program Studi Kebidanan Universitas Batam, 2020)
Hospitals, apart from medical referral centers, also have the potential to transmit infections which are often referred to as Healthcare Associated Infections (HAIs). HAIs are a major problem faced worldwide and their incidence is increasing. The incidence of HAIs in hospitals in Asian countries is around 3-21% with an average of 9%. In Indonesia, the average incidence of HAIs is around 9.1% higher than in Asian countries. The incidence of HAIs in government hospitals is 55.1%, private hospitals 35.7%, and ABRI hospitals 9.1%. Currently, the incidence of HAIs is used as a benchmark for the quality of hospital services. One of the steps in infection prevention and control is through hand hygiene. The purpose of this study was to determine whether there was a relationship between knowledge and attitudes of health workers on compliance with hand hygiene. This study used an analytical research design with a cross sectional approach and was carried out at the Raja Ahmad Tabib Hospital Tanjungpinang on July 16-30 2019. The sample in this study was 80 respondents with purposive sampling technique. From the results of the study, the majority of health workers have good knowledge (80%), the majority of health workers have good attitudes (77.5%), and most health workers comply with hand hygiene (65%). between knowledge and adherence to hand hygiene where p = 0.000 <0.05 and there is a relationship between attitudes towards compliance with hand hygiene where p = 0.000 <0.05. In conclusion, there is a relationship between knowledge and attitudes of health workers to compliance with hand hygiene. Suggestions that respondents can increase compliance to always do hand hygiene in order to reduce the incidence of HAIs in hospitals.